2013
DOI: 10.1007/s00417-013-2412-6
|View full text |Cite
|
Sign up to set email alerts
|

Patient preference of ranibizumab treatment regimen for neovascular age-related macular degeneration — monthly injections versus pro re nata

Abstract: We identified two groups of patients of considerable size who would prefer either monthly injections or as-required. Overall, there was a high acceptance rate despite a high treatment burden. Nevertheless, efforts should be undertaken to improve examination and injection procedures and to consider the patient's preference for a treatment regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 5 publications
2
29
2
1
Order By: Relevance
“…Concurring with reported high levels of treatment compliance 23 participants of this study continued with the treatment even when experiences of pain or discomfort were reported, illuminating a deep association between compliance and fear of blindness. 16,26 A fear of blindness Living with neovascular ARMD: the patient's story C McCloud and S Lake was pervasive in this study population, and more than one participant felt that death would be preferable to living with the limitations of blindness, which was a finding that resonated with suicide ideation following vision loss described by Casten and Rovner in 2008.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Concurring with reported high levels of treatment compliance 23 participants of this study continued with the treatment even when experiences of pain or discomfort were reported, illuminating a deep association between compliance and fear of blindness. 16,26 A fear of blindness Living with neovascular ARMD: the patient's story C McCloud and S Lake was pervasive in this study population, and more than one participant felt that death would be preferable to living with the limitations of blindness, which was a finding that resonated with suicide ideation following vision loss described by Casten and Rovner in 2008.…”
Section: Discussionmentioning
confidence: 66%
“…23,24 Analysis commenced after the first five interviews and was consistent with constant comparison technique where new data was examined in light of the emerging themes. The use of constant comparison techniques enhanced the 'fit' between data and developing themes and added to the trustworthiness of the findings.…”
Section: Thematic Analysismentioning
confidence: 99%
“…This is consistent with the findings of a questionnaire survey performed on patients in Cologne, Germany where patients again expressed preference for bi-monthly rather than monthly visits. 17 Patients also expressed a preference for shorter waiting times, as a survey of Spanish patients also found, 18 but this was less important than attending once every 8 weeks. Preference for doctor injectors was low and this broadly supports the use of training nurses to perform intravitreal injections.…”
Section: Discussionmentioning
confidence: 99%
“…For ranibizumab, one trial showed that only 6% of subjects typically require monthly dosing, while the remainder can be treated less frequently using an individualized approach [10] . Thus, real-life treatment of nAMD is typically individualized for most subjects following initial monthly treatment [11][12][13] , with clear benefits seen with early treatment [14] . Indeed, individualized dosing is recommended in the prescribing information for ranibizumab and the intervals between doses can be extended according to the treating physician's opinion and an assessment of disease severity [11] .…”
Section: Introductionmentioning
confidence: 99%